Characteristics of Mandibular Oral Squamous Cell Carcinoma at Oral and Maxillofacial Surgery Department Hasan Sadikin General Hospital, January 2017 – 2023 - Limanthara, Khriztie; Yusuf, Harmas Yazid; Arumsari, Asri; Putri, Dian Maifara (Odonto : Dental Journal, 2024)
Background: Oral cancer is a highly prevalent cancer with a high incidence rate around the globe. Squamous cell carcinoma accounts for 90–95% of cases of oral cancer. With a tendency to spread rapidly, it primarily affects the palate, mandible, lower lip, tongue, and floor of the mouth The elevated frequency of occurrences emphasizes the necessity for a study to investigate the attributes of mandibular squamous cell carcinoma, particularly within the Oral and Maxillofacial Surgery Department at Hasan Sadikin General Hospital in Bandung.Method: This study adopts a retrospective descriptive approach, utilizing secondary data from medical records from patients diagnosed with mandible squamous cell carcinoma from January 2017 to 2023, based on histopathological examination results.Result: Over 48-year-olds are the most common age group affected by mandible squamous cell carcinoma, accounting for 69% of cases. Males account for 51% of cases. Bandung, West Java, has the highest incidence, with 16 cases. Treatment mainly consists of surgery and chemotherapy/radiotherapy, with the mandibular corpus being the most frequent site, affecting 84% of cases.Conclusion: There were 45 patients diagnosed with mandibular squamous cell carcinoma at Hasan Sadikin General Hospital in Bandung between January 2017 - January 2023. The data was analyzed based on the age, gender, domicile, therapy, and specific location within the mandible in order to determine the distribution of these cases.